Differential Effects of Various Androgens on Polycystic Ovary Syndrome - de Medeiros, Sebastião Freitas; Barbosa, Bruna Barcelo; de Medeiros, Ana Karine Lin Winck Yamamoto; de Medeiros, Matheus Antônio Souto; Yamamoto, Márcia Marly Winck (Hormone and Metabolic Research, 2021)
The hyperandrogenism in polycystic ovary syndrome (PCOS) is associated with the risk for the future development of the cardiovascular disease. The objective of the study is to verify whether different androgens have the same harmful effect. This cross-sectional study enrolled 823 women with PCOS: 627 (76.2%) with biochemical hyperandrogenism and 196 (23.8%) with normal androgen levels. The role of individual androgen was evaluated using univariate and multivariate logistic regression. In normoandrogenemic PCOS (NA-PCOS), free androgen index (FAI) predicted significant abnormality in visceral adipose index (VAI, OR=9.2, p=0.002) and dehydroepiandrosterone (DHEA) predicted against alteration in β-cell function (OR=0.5, p=0.007). In hyperandrogenemic PCOS (HA-PCOS), FAI predicted derangements in waist triglyceride index (WTI), VAI, and lipid accumulation product (LAP) (OR ranging from 1.6 to 5.8, p<0.05). DHEA weakly predicted against VAI (OR 0.7, p=0.018), dehydroepiandrosterone sulfate (DHEAS) tended to predict against the conicity index (OR=0.7, p=0.037). After multiple regression, FAI retained significant strength to predict various anthropometric and metabolic abnormalities (OR ranging from 1.1 to 3.0, p<0.01), DHEA was kept as a protector factor against WTI, LAP, and VAI (OR ranging from 0.6 to 0.9; p<0.01) and DHEAS against the conicity index (OR=0.5, p<0.001). In conclusion, the free androgen index was the most powerful predictor of anthropometric and metabolic abnormalities of polycystic ovary syndrome. Conversely, DHEA and DHEAS demonstrated protective effects against disorders in some markers of obesity and abnormal metabolism.
Keywords: polycystic ovary syndrome; biomarkers; metabolism; hyperandrogenism; hyperinsulinemia; anthropometry